2020
DOI: 10.36720/nhjk.v9i2.186
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support on Treatment Adherence in Tb Patients: A Systematic Review

Abstract: Background: Adherence to treatment regimens in TB patients was carried out by using a pharmacological and non-pharmacological approach or paying attention to the social aspects of the patient.Objective: This review is to analyze and identify the literature related to the social support approach to treatment adherence in TB patients.Design: The systematic design of this review is to find and review journal articles from the database using Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For further research, the development of interventions to improve adherence to TB patients needs to consider these social aspects. 17 The results of research that support this research, showed that there was a significant relationship between family support and compliance with tuberculosis medication at BKPM Patidan, that family support that lacked the opportunity to not comply with medication was 5,800 times. The results on 134 respondents at the Eradication of Lung Disease (BP4) or Karangtembok Hospital Surabaya showed that there was a relationship between family support and increasing compliance with drinking OAT in tuberculosis patients (p = 0.001).…”
Section: Resultsmentioning
confidence: 52%
“…For further research, the development of interventions to improve adherence to TB patients needs to consider these social aspects. 17 The results of research that support this research, showed that there was a significant relationship between family support and compliance with tuberculosis medication at BKPM Patidan, that family support that lacked the opportunity to not comply with medication was 5,800 times. The results on 134 respondents at the Eradication of Lung Disease (BP4) or Karangtembok Hospital Surabaya showed that there was a relationship between family support and increasing compliance with drinking OAT in tuberculosis patients (p = 0.001).…”
Section: Resultsmentioning
confidence: 52%
“…Patients expect well recovery of their illness and being able to carry out daily activities including religious activities. The recovery of TB patients influence by internal factors such as patients' self-motivation and intention, and also external factors such as support from families and health care workers, including the management of psychological stress [26], [27] as well as support from peers/fellow TB patients [28]. There was an advance change of TB management due to COVID-19 pandemic, including TB patients and caregivers that have responsibility of their self care.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with a systematic review study on the role of social support on treatment adherence in patients with TB. 18 The study established that social support that includes family support, peer support and support from health workers is one of the driving factors for treatment adherence in patients with TB. This emphasises how crucial it is to include family members or other caregivers in the patient's care and treatment plan to support and encourage medication adherence.…”
Section: Bmj Public Healthmentioning
confidence: 99%